Caracterisation des savanes d`une region des Llanos Orientaux de Colombie : Memoire de fin d`etudes, Cali, Colombie du 26 juin 1994 au 7 novembre 1994 - Grollier, C (International Center for Tropical Agriculture, 1994)
Estern Colombia, the Llanos, is constituted of broad grass formations. These big expanses of savannahs present a huge potential for extensive bovine breeding. Unfortunately, these natural pastures have a low productivity and a feeble quality, due to low fertility soils with a deficiency in phosphorus and a hgih acidity. In regard to the importance of the breeding for the region, it`s essential to know the savannahs `characteristics in order to ameliorate the exploitation which is done of them. To this end, a qualitative study of the vegetation was conducted in the Puerto López region in altillanura and serranía zones. If led to the recognition of 190 species. A Factorial Analysis of the Correspondeces, effected with 104 floristic surveys cards elaborated during the investigation of 29 sites, allow to characterise eight vegetal groups. To explicate these groups, soils surveys were realised and inquiries about exploitation conditions (frequency of the fires, number of animals per hectare) leaded. A quantitative study have to be consider to classify savannahs pastures potentialities